Muhammad Abduh’s Concept about The Implementation of 20th Century Islamic Education - Annida Fitriana; Syahidin Syahidin (Perhimpunan Intelektual Muslim Indonesia, 2021)
Muhammad Abduh was a leading Islamic reformer in the 20th century. Through his ideas, Muhammad Abduh was able to reconstruct exciting Islamic understanding, both in terms of culture and aqidah, including Islamic education. The reconstruction of Islamic Education cannot be done with the awakening of the ideas and programs of Islamic modernism because it becomes the basic framework behind Islamic modernism as a whole, both modernism in thought and Islamic institutions, which are a prerequisite for the awakening of the Muslims in modern times. Therefore, Islamic thought and institutions, including education, must be modernized or reconstructed following the modernity framework; maintain Islamic institutional thinking; with Muhammad Abduh, who initiated modern education. Abduh's thoughts had a profound influence on the lives of Muslims, both in the country where he was born in Egypt, as well as in other Arab worlds, even to the Muslim world outside the Arab world such as Indonesia. The birth of reform movements, such as Muhammadiyah, Al-Irsyad, and Persatuan Islam (PERSIS), cannot be separated from the influence of Muhammad Abduh's thoughts on modernism and have become many references for western thinkers.